Cristiano Ronaldo vs. Lionel Messi : Soccer Legends Face Off - Bischer, Karen (North Mankato, MN : Capstone Press, 2025)
"Cristiano Ronaldo and Lionel Messi are soccer superstars! Between the two, Ronaldo has more career goals, but Messi leads in career assists. So which one is the all-time best? Young readers can decide for themselves by comparing the fantastic feats and stunning stats of two legendary pro soccer players"--
Soccer legends face off! -- Heights and speed -- Matches played -- Goals -- Assists -- UEFA performances -- La Liga performances -- Hat tricks -- El Clásico performances -- World Cup performances -- Match-winning goals -- Ballon d'Or awards -- Who Is the best?
Includes bibliographical references and index.
Keywords: Ronaldo, Cristiano, -- 1985- -- Juvenile literature; Messi, Lionel, -- 1987- -- Juvenile literature; Soccer players -- Biography -- Portugal; Biography -- Argentina; Sports and games